The Ecdysone and Notch Pathways Synergistically Regulate Cut at the Dorsal–Ventral Boundary in Drosophila Wing Discs. (20th April 2016) - Jia, Dongyu; Bryant, Jamal; Jevitt, Allison; Calvin, Gabriel; Deng, Wu-Min
Abstract: Metazoan development requires coordination of signaling pathways to regulate patterns of gene expression. In Drosophila, the wing imaginal disc provides an excellent model for the study of how signaling pathways interact to regulate pattern formation. The determination of the dorsal–ventral (DV) boundary of the wing disc depends on the Notch pathway, which is activated along the DV boundary and induces the expression of the homeobox transcription factor, Cut. Here, we show that Broad (Br), a zinc-finger transcription factor, is also involved in regulating Cut expression in the DV boundary region. However, Br expression is not regulated by Notch signaling in wing discs, while ecdysone signaling is the upstream signal that induces Br for Cut upregulation. Also, we find that the ecdysone-Br cascade upregulates cut-lacZ expression, a reporter containing a 2.7 kb cut enhancer region, implying that ecdysone signaling, similar to Notch, regulates cut at the transcriptional level. Collectively, our findings reveal that the Notch and ecdysone signaling pathways synergistically regulate Cut expression for proper DV boundary formation in the wing disc. Additionally, we show br promotes Delta, a Notch ligand, near the DV boundary to suppress aberrant high Notch activity, indicating further interaction between the two pathways for DV patterning of the wing disc.